(untitled) (LACCEI, 2024)
The objective of this research is to determine the physical and mechanical properties of artisanal brick with natural aggregate containing iron particles, 2022. The methodology used according to its purpose is considered applied, with a quantitative approach and experimental design, descriptive in scope and insofar as the study period is cross-sectional, selecting a sample of 300 bricks made with the addition of 10%, 25%, 50% and 75% of natural aggregate containing iron particles. To achieve the objective of the investigation, the physical properties of the Standard Sample (MP), of the natural aggregate containing iron particles (MH), of the samples with increases of 10%, 25%, 50% and 75% will be previously reduced. from (MH) After carrying out the soil mechanics tests, we proceeded with the elaboration of artisan bricks. Subsequently, the study units were subjected to laboratory tests to determine the physical and mechanical properties of the handmade brick made with the Standard Sample (MP) and with the addition of 10%, 25%, 50% and 75% of (MH). The results showed that the sample with an increase of 10% of MH, satisfies the requirements of the NTP-E.070 of Masonry, in terms of dimensional variation, warpage and absorption Likewise, the compressive strength in units increases by 36.40% and the compressive strength in masonry piles by 4.69%, in relation to the NTP E.70 for class 1 bricks and in relation to the standard sample, the increase was 50.80% and 53.43%.